Cheerleading exercises influence on 5-9th forms the schoolchildren's coordination abilities - Tetiana Bala (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to study cheerleading influence on individual demonstration types of coordination abilities for pupils of 5-9 forms. Materials and Methods: theoretical analysis and generalization of scientific and methodical literature, pedagogical testing, pedagogical experiment and mathematical statistics methods. Results: indicators of the development level of the ability to control the movements by the dimensional and temporal parameters, as well as degree of their change under Cheerleading training influence for pupils of 5-9 forms of a secondary school are presented. Conclusions: cheerleading usage had a positive influence on the degree of demonstration of individual forms of coordination abilities for secondary school pupils